Financial Ratio Analysis to Measure the Financial Performance of the Banking Sector in Indonesia - Indrayani, Lioni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this study is to analyze the ratio of liquidity, solvency, and activity for the measurement of financial performance. The data analysis method is comparative descriptive analysis. The bank financial statements then analyzed the liquidity, solvency, activity, and profitability for comparison of results in each year and will be adjusted to Bank Indonesia (BI) standard that can be analyzed to measure the financial level and performance of the bank. While the data source used in this study is secondary data in the form of bank financial statement documents from 2015 to 2019 obtained from the website www.IDX.co.id. The results show bank liquidity can meet the short term on time. The result of solvency is seen as the ability of a bank in fulfilling and keep its ability to always fulfill its obligation in paying the debt on time. The profitability of banks has a good ratio.